2002
DOI: 10.1039/b110953g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and PM-IRRAS studies of potential controlled transformations of phospholipid layers on Au(111) electrodes

Abstract: Chronocoulometry and photon polarisation modulation infrared reflection absorption spectroscopy (PM-IRRAS) have been employed to study the fusion of dimyristoylphosphatidylcholine (DMPC) vesicles onto a Au(111) electrode surface. The results show that fusion of the vesicles is controlled by the electrode potential or charge at the electrode surface (s M ). At charge densities of À15 mC cm À2 < s M < 0 mC cm À2 , DMPC vesicles fuse to form a condensed film. When s M < À15 mC cm À2 , de-wetting of the film from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 73 publications
(109 reference statements)
11
88
0
Order By: Relevance
“…In this potential-dependent study of the adsorption process of cyanide ions on a silver electrode showed differences between the species adsorbed directly on the electrode surface and those dissolved in the electrolyte solution [82]. Later, structural aspects of the potential-driven adsorption-desorption process of amphiphilic organic films adsorbed on the gold electrode surface were investigated in detail [29,30,32,51].…”
Section: Polarization Modulation Infrared Reflection Absorption Spectmentioning
confidence: 98%
See 4 more Smart Citations
“…In this potential-dependent study of the adsorption process of cyanide ions on a silver electrode showed differences between the species adsorbed directly on the electrode surface and those dissolved in the electrolyte solution [82]. Later, structural aspects of the potential-driven adsorption-desorption process of amphiphilic organic films adsorbed on the gold electrode surface were investigated in detail [29,30,32,51].…”
Section: Polarization Modulation Infrared Reflection Absorption Spectmentioning
confidence: 98%
“…The beam convergence was set to ± 5%; comparable with the beam convergence in commercially available IR spectrometers. The wavenumber of the incoming IR radiation was set to 2900 cm −1 ( = 3.44 μm), corresponding to absorption modes of CH groups, the most often analyzed spectral region in organic molecules adsorbed on solid surfaces [12,32,51,[58][59][60][61]. Figure 2 shows the three-dimensional plot of the MSEFS as a function of the angle of incidence and electrolyte layer thickness.…”
Section: Application Of Irras To the Electrochemical Interface: Theormentioning
confidence: 99%
See 3 more Smart Citations